Effects of chitosan coating combined with essential oils on quality and antioxidant enzyme activities of grass carp (Ctenopharyngodon idellus) fillets stored at 4 °C. (13th November 2016) - Yu, Dawei; Xu, Yanshun; Jiang, Qixing; Xia, Wenshui
Summary: Effects of chitosan coating combined with essential oils from clove, cinnamon and lemon grass on quality and antioxidant enzyme activities of grass carp fillets stored at 4 ± 0.5 °C were evaluated. The quality parameters (including pH, total volatile basic nitrogen (TVB‐N), K value, thiobarbituric acid (TBA) value, shear force and total viable count (TVC)) and antioxidant enzyme activities were analysed periodically. The results indicated that composite chitosan coatings presented better preservation effects than chitosan coating alone. In addition, chitosan–clove essential oil coating had the best quality enhancement effects among treatments by inhibiting deterioration of physicochemical quality and microbial growth and maintaining antioxidant enzyme activities of fillets during refrigerated storage. The negative correlation was observed between the changes in TBA values and antioxidant enzyme activities in fillets. Based on these findings, chitosan–essential oil coatings effectively mitigated oxidative stress and extended shelf life of refrigerated grass carp fillets. Abstract : Chitosan based coatings contribute to reduce the oxidative damage of refrigerated grass carp fillets due to their protective effects to antioxidant enzyme activities as well as antioxidant capacity in vitro of essential oils.